Pengaruh aplikasi pasta casein phosphopeptide amorphous calcium phosphate pada white spot gigi desidui - AFANTY, Alfia ([Yogyakarta] : Universitas Gadjah Mada, 2009)
White spot is a condition of teeth like chalky-white, opaque areas due to demineralizing process of bottom layer within email surface. White spot is early process of caries, so it need to manage lession in order not to enlarge and occurs cavity. One effort to avoid incidence of caries for white spot-experiencing teeth was by applying Casein Phosphopeptide Amorphous Calcium Phosphate (CPP-ACP) above email surface. This case study was to indicate effect of Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) paste application in white spot of deciduous teeth. Based on three patients, A, B, and C aged 3 – 6 years old with white spot disorder within labial surface of anterior deciduous teeth. Teeth experienced white spot was applied with CPP-ACP paste using 32 application for 3 months. Clinical evaluation for first, second, and third month was conducted to measure white spot area before and after application. Periodic evaluation of patient A, B and C in third month indicated that there was a decreased area and color change in white spot after applied by paste CPP-ACP amounted 32 times. In this case, it could be concluded that color change in white spot was followed by change of area in white spot. White spot would be seen in same color with color of non-affected teeth, namely transparent white. So, white spot area would be seen to decrease and then disappeared.